Accessories to modernity : fashion and the feminine in nineteenth-century France - Hiner, Susan (EBL-Schweitzer, 2010)
Examining fashion accessories in both novels and fashion discourses, Susan Hiner reframes the feminine accessory as a signifier of modernity and makes an important claim about the "accessory" status of women in nineteenth-century France: as both commodities and consumers, women were in fact "accessories to modernity."